Facet-Guided in-Plane Metal Plating via Accelerated Surface Diffusion in Mg Metal Batteries - Ryu, Hee Seung; Lee, JunWon; Kim, Seonju; Choi, Kiwon; Jo, Hyeonmin; Lee, ByeongHyeon; Park, Jungjae; Ko, Min Jae; Lim, HyungKyu; Lim, HeeDae (Wiley-VCH Verlag, 2025)
Anode-free metal batteries offer the highest theoretical energy density on the anode side. However, their practical deployment is severely limited by uncontrolled metal plating and dendritic growth. These challenges stem from the inherently high-entropy nature of metal deposition and the restricted in-plane surface diffusion of metal adatom. Herein, a facet-guided fundamental strategy is presented to promote lateral metal growth by tailoring the crystallographic orientation of the host. Specifically, the Zn(002) facet, which exhibits excellent lattice compatibility with Mg metal, offers near-zero diffusion barriers, facilitating rapid in-plane adatom migration and promoting uniform metal deposition. Through combined experimental characterization and theoretical validation, it is demonstrated that this controlled deposition approach effectively suppresses dendrite formation and significantly improves electrochemical reversibility. These findings underscore the potential of crystallographic engineering to achieve stable metal plating in anode-free architectures, providing broadly applicable insights for various metal battery chemistries.